(untitled) (Baltic Journal of Sport and Health Sciences, 2026)
Purpose: This study aimed to co-create an innovative approach to increase physical activity (PA) and reduce sedentary behaviour (SB) among older adults living in community and nursing homes. Methods: This qualitative study followed COREQ guidelines and is part of a registered mixed-methods project (NCT06100835). Thirteen face-to-face focus groups and three online interviews were conducted with 98 participants (51 older adults, 5 caregivers, 29 professionals, 3 students, and 10 policymakers) in Spain, Denmark, Germany, France, and Italy. We explored diverse perspectives of participants to understand their barriers and motivators for PA, and design features for the programme that enhance enjoyment and social inclusion. The Octalysis framework served as a practical tool for exploring behavioural motivators, guiding the co-creation of programme elements that enhance enjoyment and adherence. Data were collected using semi-structured guides, then transcribed, translated, and analysed following Braun and Clarke’s method for reflexive thematic analysis to identify key themes. Results: Five main topics were identified: 1) Varied experiences and meanings of PA, often extending beyond structured exercise to daily movement; 2) Personal motivators (enjoyment, social interaction, and maintaining function) and individual barriers (pain, fear of injury, and bad surrounding conditions) to engage in PA; 3) Systemic and environmental barriers, such as staffing limitations and inadequate facilities; 4) Strategies for enjoyable programmes, emphasising skilled and adaptive facilitators, personalisation, and group dynamics; 5) Approaches to social inclusion, highlighting the need for cultural sensitivity and support for cognitive impairment. These findings informed the design of the JOIN4JOY intervention for pilot testing. Conclusion: This study shows the potential of co-design and gamification to create PA programmes that are both engaging and inclusive for older adults. By tailoring interventions to personal preferences and local contexts, this approach enhances participation and helps overcome structural and social challenges. The findings have implications for future practice and development of effective, context-sensitive programmes for active and healthy ageing across Europe. Support/Funding Source: This research is part of the JOIN4JOY project, co-funded by the European Commission under the Erasmus+ Sport programme (Grant Number 101050505).